CLIMATE CHANGE AND DENGUE IN INDONESIA: A SYSTEMATIC REVIEW - Fajar Fatmawati; Sulistyawati Sulistyawati (Universitas Ahmad Dahlan, 2019)
Background: Climate change is a global issue because of its impact on environmental and human health. No exception for Indonesia, an archipelago state with a tropical climate. Climate change potentially influences the mosquitos borne disease, including dengue fever, which poses a vulnerability to the Indonesian populations. This article aims to review the association and the impact of climate change to dengue fever, particularly in Indonesia and to inform the policymaker on directing the adaptation option.Methods: Of thirteen peer review articles were included in this review sourced from google scholar database.Results: Climate change affects dengue incidence in Indonesia due to climate variability.Conclusions: It is essential to Strengthen the surveillance system and provide an early warning system (EWS) based on climate information.Keywords: Climate change, dengue, Indonesia